Leadership Pesantren: Urgensi Pendidikan dalam Menyiapkan Pemimpin Bangsa Berkualitas dan Bermoral - Siti Rodliyah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
People views on the role of education in pesantren has shifted over years. Previously, people thought that pesantren education was the second class. However, the profile of pesantren alumni and their contribution in various aspects of leadership in societies has proven that pesantren education contribute to nation development. People believe that pesantren is not an alternative education institution, but the major education provider to graduate well qualified human resources with leadership skill, as well as mastering both emotional and spiritual intelligent (ESQ). Besides essential to improve human development index of a country, ESQ is a pivotal element for a leader. This is in line with the argument of this paper that pesantren education even in this globalized era is able to produce the prospective leaders rich with relevant skills and intellectuality as well as deep understanding of kitab kuning (yellow book) as the classical Islamic intellectual literature and tailor it with modern science and technology. In turn, pesantren is able to groom well qualified, dignified, and have strong morality of prospective leaders in the globalized era.